The use of financial graphics as an impression management tool: evidence of Portuguese listed companies - Azevedo, G. M. C.; Oliveira, J. S. O.; Ferreira, A. C. S.; Dias, S. R. P. M. (International financial reporting standards and new directions in earnings management, 2019)
The main objective of this chapter is to determine the graph discrepancy index and to analyze which factors can actually influence the graphical discrepancy index, based on the strategies of impression management. For this particular purpose, a content analysis of management and financial reports was made, from 2010 to 2015, of Portuguese companies with securities admitted to trading in Euronext Lisbon. Findings indicate that companies tend to engage in printing management practices, but it was not possible to identify the determinants of such practices since all the hypotheses were rejected.